Varieties of capitalism and varieties of macroeconomic policy. Are some economies more procyclical than others? - Bruno Amable; Karim Azizi (Max Planck Institute for the Study of Societies, 2011)
The role of macroeconomic policy in the different varieties of capitalism has been largely ignored. Recent contributions to the literature have argued that nonliberal economies should be expected to have less accommodating (i.e., less countercyclical) macroeconomic policies than liberal varieties. Using time-series cross-section data on 18 OECD countries between 1980 and 2002, this paper tests that hypothesis and, more particularly, whether the reaction of discretionary fiscal policy to macroeconomic shocks is conditioned by variables that differentiate liberal from nonliberal varieties of capitalism: the degree of generosity of the social protection system, the degree of coordination of wage bargaining, and the fragmentation of the political party system. The test results do not support the conclusion that nonliberal economies' macroeconomic policy would be less countercyclical than that of liberal economies. On the contrary, discretionary fiscal policy has been more countercyclical in countries with a fragmented political system or a generous social protection system. – – Die Rolle makroökonomischer Politik in unterschiedlichen kapitalistischen Systemen wurde bisher nur selten eingehend untersucht. Eine neuere Argumentation vertritt die These, dass die makroökonomische Politik in nichtliberalen Ökonomien weniger antizyklisch ausfällt als in liberalen Ökonomien. Das Papier prüft diese These anhand einer gekreuzten Längs- und Querschnittanalyse für 18 OECD-Länder im Zeitraum von 1980 bis 2002. Dabei widmet es sich im Besonderen der Frage, inwieweit finanzpolitische Reaktionen auf makroökonomische Schocks von jenen Variablen beeinflusst werden, die liberale von nichtliberalen Ökonomien unterscheiden: die Generosität des Wohlfahrtssystems, das Ausmaß der Koordinierung von Lohnverhandlungen und der Grad der Fragmentierung des Parteiensystems. Das Ergebnis bestätigt die These nicht, sondern zeigt, dass eine diskretionäre Fiskalpolitik in jenen Ländern antizyklischer ausfällt, die über ein fragmentiertes Parteiensystem oder ein generöses Wohlfahrtssystem verfügen.
Keywords: 300